2021
DOI: 10.3389/fphar.2021.737137
|View full text |Cite
|
Sign up to set email alerts
|

Five-Decade Update on Chemopreventive and Other Pharmacological Potential of Kurarinone: a Natural Flavanone

Abstract: In the present article we present an update on the role of chemoprevention and other pharmacological activities reported on kurarinone, a natural flavanone (from 1970 to 2021). To the best of our knowledge this is the first and exhaustive review of kurarinone. The literature was obtained from different search engine platforms including PubMed. Kurarinone possesses anticancer potential against cervical, lung (non-small and small), hepatic, esophageal, breast, gastric, cervical, and prostate cancer cells. In viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 72 publications
0
23
0
Order By: Relevance
“…IC 50 = 2-62 µM in cervical, lung (non-small and small), hepatic, esophageal, breast, gastric, cervical, and prostate cancer cells 20-500 mg/kg in vivo in lungs (non-small and small) cancer. Higher selectivity toward cancer cells in comparison with respective normal cells [195].…”
Section: Kurarinonementioning
confidence: 99%
“…IC 50 = 2-62 µM in cervical, lung (non-small and small), hepatic, esophageal, breast, gastric, cervical, and prostate cancer cells 20-500 mg/kg in vivo in lungs (non-small and small) cancer. Higher selectivity toward cancer cells in comparison with respective normal cells [195].…”
Section: Kurarinonementioning
confidence: 99%
“…Dietary compounds also regulate cell cycle progression, inflammatory cytokines, and oxidative stress response in cancer cells, and have the potential to modulate small non-coding RNAs’ expression alone or in a synergistic manner. More importantly, dietary phytochemicals have a greater ability to prevent/inhibit the formation of a small population of cancer cells often referred to as cancer stem-like cells by targeting various signaling pathways [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Therefore, targeting the luminal A-derived BCSCs by dietary phytochemicals could be a better strategy in the prevention and clinical management of breast cancer.…”
Section: Relevance Of Targeting Luminal A-derived Breast Cancer Stem ...mentioning
confidence: 99%
“…8 Kurarinone is one of natural flavonoids found in many plants such as Sophora angustifolia, and has multiple pharmacological potentials. 9 Previous reports have suggested that kurarinone has anti-carcinogenic property, 10,11 anti-inflammatory activity, 12 neuro-protective activity, 13 and anti-oxidative activity. 14,15 Hence, we hypothesized that kurarinone might regulate oxidative stress-induced granulosa cell dysfunction based on its anti-oxidative property.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional Chinese medicines have rescue effects on granulosa cell apoptosis in ovarian failure, including follicular atresia 8 . Kurarinone is one of natural flavonoids found in many plants such as Sophora angustifolia , and has multiple pharmacological potentials 9 . Previous reports have suggested that kurarinone has anti‐carcinogenic property, 10,11 anti‐inflammatory activity, 12 neuro‐protective activity, 13 and anti‐oxidative activity 14,15 .…”
Section: Introductionmentioning
confidence: 99%